Productive, reproductive, and estrus characteristics of different breeds of buffalo cows in Bangladesh - Rashid, Mohammad Harun Or; Sarkar, Anup Kumar; Hasan, Mir Md Iqbal; Hasan, Moinul; Juyena, Nasrin Sultana (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The objective of this research work is to know the productive and reproductive performances and problems of local, crossbred, Nilli, and Murrah buffalo cows in selected study areas in Bangladesh. Methodology: A total of 1,241 local, crossbred, Nilli, and Murrah buffalo cows were surveyed in the selected areas with a pre-set questionnaire. Among 1,241 buffalo cows, 112 buffalo cows were randomly selected at day 0 of the estrus cycle for studying ovarian features. Results: Results showed that the average age, body condition score, and body weight were significantly (p < 0.05) different among the studied breeds. Milk production in Murrah and lactation length in Nilli cows were significantly (p < 0.05) higher than indigenous, crossbred, Nilli, and indigenous, crossbred, Murrah buffalo cows, respectively. Results also illustrated that sexual maturity, estrus cycle length, insemination time after the onset of estrus, and gestation length insignificantly (p > 0.05) varied among the surveyed breed. But, the fallout of the study denoted that estrus duration, first calving age, parity number, number of service per conception, calving interval, and voluntary waiting period varied significantly (p < 0.05) in different breeds. Ovarian physiological characteristics such as vaginal electrical resistance, average number of follicles in two ovaries, and largest follicular diameter, estrogen, and progesterone at day 0 of the estrus cycle of local, crossbred, Nilli, and Murrah buffalo cows showed insignificantly (p > 0.05) differences. Conclusion: The study will help the veterinarian and researcher to identify the constraints for the reproductive efficiency of buffalo in Bangladesh. J. Adv. Vet. Anim. Res., 6(4): 553-560, December 2019